2012
DOI: 10.1016/j.powtec.2012.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Influence of lactose carrier particle size on the aerosol performance of budesonide from a dry powder inhaler

Abstract: The purpose of this study was to evaluate the effect of carrier particle size on properties of dry powder and its effect on dry powder inhaler (DPI) performance. Commercial α-lactose-monohydrate, a commonly used carrier in DPI formulations, was carefully sieved to obtain different lactose size fractions, namely Lac A (90–125 μm), Lac B (63–90 μm), Lac C (45–63 μm), Lac D (20–45 μm), and Lac E (< 20 μm). The lactose samples were analysed in terms of size, shape, solid state, density, and flowability. Lactose pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
70
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(76 citation statements)
references
References 30 publications
6
70
0
Order By: Relevance
“…In order to aerosolize the drug particles, the properties of both the carriers and the API particles are of great importance since the drug-carrier adhesive forces need to be overcome by the patient's inspiratory force [4]. Studies have reported on the impact of particle mean size [5], particle size distribution [6], morphology [7,8], crystal form [9], surface roughness [10] and surface energy [11] on the performance of inhalable dry powders. Indeed, the particle size, size distribution, morphology and polymorphism of carriers have been found to exert a major impact on the efficiency of dry powder inhalation (DPI) [12,13], although results have not been consistent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to aerosolize the drug particles, the properties of both the carriers and the API particles are of great importance since the drug-carrier adhesive forces need to be overcome by the patient's inspiratory force [4]. Studies have reported on the impact of particle mean size [5], particle size distribution [6], morphology [7,8], crystal form [9], surface roughness [10] and surface energy [11] on the performance of inhalable dry powders. Indeed, the particle size, size distribution, morphology and polymorphism of carriers have been found to exert a major impact on the efficiency of dry powder inhalation (DPI) [12,13], although results have not been consistent.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the particle size, size distribution, morphology and polymorphism of carriers have been found to exert a major impact on the efficiency of dry powder inhalation (DPI) [12,13], although results have not been consistent. For instance, Podczeck [14] found that small particles improved aerosol performance, while Kaialy et al [5] observed that large particles had such an effect. Further, Maas et al [15] and Kaialy et al [16] found that smooth carriers provided a higher fine particle fraction (FPF) than rough carriers, while Littringer et al [17] showed that rough surface carriers improved the FPF.…”
Section: Introductionmentioning
confidence: 99%
“…The particle-particle interaction forces have to be sufficiently strong that fine API particles can adhere with the carriers or form large agglomerates to be transported, but weak enough that they can be detached or dispersed by a deagglomeration process and thus allow the delivery of the API particles into the respiratory tracts and lungs. Therefore, particle-particle interactions play a significant role in controlling the performance of DPIs and hence many studies have been performed to explore the dependency of these interactions on particle size [7,8], material properties [9,10], particle concentration [11,12], particle morphology [13,14], particle surface roughness [15,16], storage conditions [17,18], surface area [19], density and porosity [20], and crystal form [21]. For example, Kaialy et al [7] experimentally examined the influence of the particle size of lactose carrier on the DPI performance and demonstrated that the DPI performance improved with decreasing carrier particle size.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, particle-particle interactions play a significant role in controlling the performance of DPIs and hence many studies have been performed to explore the dependency of these interactions on particle size [7,8], material properties [9,10], particle concentration [11,12], particle morphology [13,14], particle surface roughness [15,16], storage conditions [17,18], surface area [19], density and porosity [20], and crystal form [21]. For example, Kaialy et al [7] experimentally examined the influence of the particle size of lactose carrier on the DPI performance and demonstrated that the DPI performance improved with decreasing carrier particle size. Young et al [11] investigated the relationship between API dosage (drug/lactose ratio) and aerosolisation performance of conventional carrier based formulations using the twin stage impinger and found that the fine particle fraction (FPF) decreased with increasing API dosage for small values of the parameter (10-135 µg/50 mg), while the FPF increased with increasing API dosage at large values of the API dosage (135-450 µg/50 mg).…”
Section: Introductionmentioning
confidence: 99%
“…Presence of lactose monohydrate types and sieve fractions as carriers is a strategy to improve dispersion properties of inhalation particles (Kaialy, Alhalaweh, Velaga, & Nokhodchi, 2012;Patil, Mahadik, & Paradkar, 2015). Blending drugs with coarse lactose not only enhances the bulk of the formulations; also it improves separation of fine drug particles from formulation to improve dosing consistency of the DPI formulations (Prime et al, 1997).…”
Section: Dpi Formulationsmentioning
confidence: 99%